Computer-guided buccal cortical plate separation for removal of calcified benign odontogenic tumors affecting the mandibular angle region - Mohammed Omara; Ayman Gouda; Sherif Ali (SpringerOpen, 2022)
Abstract Purpose Surgical removal of intra-bony calcific benign lesions is technically challenging regarding its accessibility, proximity to vital structures, and deteriorating effect on the remaining bony structures. Methods Computer-guided buccal cortical plate separation was performed for ten patients using patient-specific osteotomy locating guides and pre-bent plates. The guide was designed to outline the osteotomy, the buccal cortical plate was separated, the lesion was removed, and finally, the pre-bent plates were used to fix the separated cortex. Results Surgical procedures were uneventful for all patients, operation time was 39.5 ± 13.01 min, postoperative pain decreased within the follow-up time intervals, and there was a statistical significant difference between the time intervals (P value < 0.001). Edema and trismus were acceptable. One case showed nerve affection which resolved after 4 weeks. Conclusion Computer-guided buccal cortical plate separation for removal of intra-bony calcified benign lesions provides a promising approach, especially for inexperienced surgeons. Trial registration ClinicalTrials.gov NCT05329974 . Registered on 6 April 2022-retrospectively registered.